2022
DOI: 10.1111/inm.13032
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting knowledge of recovery‐oriented practice amongst mental health nursing and medical staff working on acute mental health inpatient units

Abstract: Over recent decades, the shift to recovery‐oriented practice has been central to mental health policy. Despite this emphasis, mental health services can struggle to meet this expectation. This study explores the knowledge and attitudes in relation to the recovery‐oriented practice of clinical staff working at an Australian acute inpatient mental health unit. The Recovery Knowledge Inventory (RKI) is a widely used self‐report tool that assesses mental health professionals' knowledge and attitudes towards recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…This theme relates to the process of professional identity formation over time. Clinical psychologists understand that their professional identities as continuously changing and being renegotiated (1,2,3,4,5,6,7,9,11,12,13,14,16,19,20,22,23). Possibly for this reason, multiple studies featured RQs pertaining directly to personal and professional development (2,3,5,10,12,14,16,21).…”
Section: Theme 3: Changes In Professional Identity Over Timementioning
confidence: 99%
See 4 more Smart Citations
“…This theme relates to the process of professional identity formation over time. Clinical psychologists understand that their professional identities as continuously changing and being renegotiated (1,2,3,4,5,6,7,9,11,12,13,14,16,19,20,22,23). Possibly for this reason, multiple studies featured RQs pertaining directly to personal and professional development (2,3,5,10,12,14,16,21).…”
Section: Theme 3: Changes In Professional Identity Over Timementioning
confidence: 99%
“…Numerous studies indicated the training and early career period is a critical stage in the process of professional identity formation and that this simultaneously comprises a period of rapid growth (2,3,6,8,9,12,16,24) and destabilisation of sense of self (4,5,6,8,9,10,12,16,21,23). This destabilisation was associated with feelings of threat, distrust, isolation and vulnerability (12,21,22) and a sense of needing to relinquish a sense of who one is (21).…”
Section: Theme 3: Changes In Professional Identity Over Timementioning
confidence: 99%
See 3 more Smart Citations